Configurational morphological attributes and co-presence in dispersed residential allotments of brazilian medium-sized cities - Bassan Marinho Maciel, Filipe (2018)
This paper aims at identifying which configurational morphological attributes have stronger correlation with co-presence in the socio-spatial context of two dispersed residential allotments in Santa Maria (RS), Brazil. Co-presence is the group of people who are together in a given space. The methodology consists of: i) axial and segment analysis of the study area with different radii; ii) measurement of co-presence levels categorized as ‘moving pedestrians’ and ‘stationary pedestrians; and iii) calculation of the Pearson correlation coefficients between co-presence and syntactic measures. It is based on the following question: how does the urban form explain the social appropriation of open spaces in dispersed settlements? The results showed that, although the two neighborhoods have different co-presence patterns, the measures of ‘integration’ and ‘choice’ have the strongest positive correlations with the number of pedestrians. The types of analysis and radius influenced the strength of the correlations: segment angular analysis with metric radius was more efficient for the largest number of categories of co-presence when these were not composed essentially by natural movement. In general, larger radii applied to local measurements generated the strongest correlations: R1000m for angular analysis, and R5 for axial analysis.